KONSEP PEMEROLEHAN BAHASA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA - Nurlaila Nurlaila (Prodi PAI STIT Sunan Giri Bima, 2021)
This paper examines the concept of language acquisition and its implications for language learning, in particular by dialogueing the theories of acquisition and learning put forward by experts. The problem that will be discussed in this paper is how humans acquire language and how they learn it, as humans acquire the true language that is how humans learn language, because language is an innate ability that humans have. Education and learning will tend to lose their spirit if in practice its implementation is not done based on need assessment, analysis of appropriate approaches and theories. Therefore, the concept of acquisition presented in this paper aims to provide an overview of the main framework of language learning for educators, learners/ learners discuss, so that it can contribute in determining methodological steps such as what to do to achieve the desired language learning targets.